Association between Serum Uric Acid Level and Metabolic Syndrome and Its Sex Difference in a Chinese Community Elderly Population. (22nd July 2014) - Liu, Miao; He, Yao; Jiang, Bin; Wu, Lei; Yang, Shanshan; Wang, Yiyan; Li, Xiaoying
Abstract : Objective . This study aimed to evaluate the association between serum uric acid (SUA) levels within a normal to high range and the risk of metabolic syndrome (MetS) among community elderly and explore the sex difference. Design and Methods . A cross-sectional study was conducted in a representative urban area of Beijing between 2009 and 2010. A two-stage stratified clustering sampling method was used and 2102 elderly participants were included. Results . The prevalence of hyperuricemia and MetS was 16.7% and 59.1%, respectively. There was a strong association between hyperuricemia and four components of MetS in women and three components in men. Multiple logistic regression analysis showed ORs of hyperuricemia for MetS were 1.67 (95% CI: 1.11–2.50) in men and 2.73 (95% CI: 1.81–4.11) in women. Even in the normal range, the ORs for MetS increased gradually according to SUA levels. MetS component number also showed an increasing trend across SUA quartile in both sexes ( P for trend < 0.01). Conclusion . This study suggests that higher SUA levels, even in the normal range, are positively associated with MetS among Chinese community elderly, and the association is stronger in women than men. Physicians should recognize MetS as a frequent comorbidity of hyperuricemia and take early action to prevent subsequent disease burden.